The Qur'anic Reading Approach to Improve Student Mental Health in Higher Education - Hasanah, Mila; Kusuma, Rudy Hadi (Angstrom Centre of Education, 2024)
Student mental health problems in higher education are an important and complex issue. The purpose of this research was to find out and measure how the approach of reading the Qur'an at the beginning of learning can improve students' mental health in Higher Education. The research design applies a 4D development research model (define, design, development, disseminate). The research sample was 250 Islamic Education Guidance and Counseling students and Madrasah Ibtidaiyah Teacher Education. Research instruments used observation, tests, interviews, and documentation. Data analysis using the Tiagarajan Model. The approach of reading the Qur'an is relevant and valid and applied to all courses. 92.78% effectiveness rate successfully improves student mental health. Especially from the aspect of Emotional balance, reasonable stress levels, life balance, good sleep quality, healthy interpersonal relationships, self-esteem, adaptability, independence, physical fitness, academic performance, self-awareness, using effective keeping, and lack of signs of mental disorders. However, this approach is only relevant for Muslim lecturers and students. Students who are Catholic/Protestant Christians, Hindus, Buddhists, and Confucians can use approaches with their respective scriptures.